EFEK PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. BESTEL SARANA TRANSPORTASI DI BATAM - Syaifullah (Journal of Social Sustainability Management, 2022)
This research was conducted based on the background of a competitive business climate and demands for improving the quality of human resources, especially in the field of outsourcing and cleaning services. This study aims to determine and analyze the effect of employee training (X) on employee performance at PT Bestel Sarana Transportasi. The research method applied is quantitative research methods. Data collection was carried out by distributing questionnaires to 57 respondents as research samples, using the Slovin formula to determine the number of research samples. In this study, the data analysis technique used validity test, reliability test, classical assumption test (normality tes and heteroscedasticity test), simple linear regression analysis test, with the help of SPSS version 20 software program. Based on the results of multiple linear regression statistical calculations, it is proven that the Training variable (X) has a positive and significant effect on employee performance (Y) with the result of Sig.count 0.000 < = 0.05.